Efektivitas model latihan fisik permainan R.A. berbasis lompat jauh untuk anak usia 13 - 15 tahun - Afrinaldi, Rolly; Prasetyo, Tommy Rizki (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Conventional training models that only focus on repetitive techniques without variety, such as static exercises or monotonous drilling, are often considered inefficient for the 13-15-year-old age group. This approach tends to be boring, lacks motivational aspects, and does not fully develop all-around motor skills as the game-based R.A. model does. This research aims to see how effective the game-based Resistance and Aerobic training (R.A.) physical training model is in the long jump for the 13-15-year-old age group, which has been developed previously. This study used a quantitative approach with a pre-experimental design (one-group pretest-posttest) to measure the model's effectiveness. The sample consisted of 60 students aged 13-15 years old who were purposively selected. The test instruments used in this research were the physical test of running 30 meters, jumping three times, dynamic balance test, and flexibility. The analysis test uses statistics (t-test) to evaluate the effectiveness of the model. The results showed a significant increase between the pretest and posttest results. These results prove that the R.A. model is more effective than the monotonous conventional method in improving physical abilities and long jump technique. This game-based approach also positively impacted overall motor skill development, making it an innovative and relevant training alternative for the 13-15 age group. These findings make an important contribution to the development of sports training methods, particularly the long jump.